Functional muscle power testing in young, middle-aged, and community-dwelling nonfrail and prefrail older adults - Zech, Astrid; Steib, Simon; Freiberger, Ellen; Pfeifer, Klaus (Archives of physical medicine and rehabilitation, 2011)
Zech A, Steib S, Freiberger E, Pfeifer K. Functional muscle power testing in young, middle-aged, and community-dwelling nonfrail and prefrail older adults. - Objective - To evaluate the stair climb (SC) and sit-to-stand (STS) transfer test for functional power assessment in young, middle-aged, and community-dwelling nonfrail and prefrail older adults. - Design - Cross-sectional study. - Setting - Sport science institute providing health-related exercise programs for older people. - Participants - Participants (N=60; age, 22-81y) were divided into groups of young (n=15; 20-30y), middle-aged (n=16; 40-60y), nonfrail older (n=16; >65y), and prefrail older adults (n=13; >65y). - Interventions - Not applicable. - Main Outcome Measures - SC and STS transfer power were measured on 2 separate occasions. - Results - Age and height correlated positively (P<.001) with both power measures. Multiple linear regression analysis showed that 67.9% (R2) of the variance in SC power and 31.3% (R2) of the variance in STS transfer power can be attributed to age and height. Significant age-related subgroup differences were found for SC power (P=.001). Nonfrail and prefrail older adults differed significantly in both power measures (P<.001). - Conclusions - The findings indicate that SC and STS transfer power are sensitive enough to distinguish between nonfrailty and prefrailty. This suggests that both tests are relevant clinical measures in older people.